Cubeb (Piper cubeba L.): nutritional value, phytochemical profiling and dermacosmeceutical properties - Drissi, Badr Eddine; Mahdi, Ismail; Ortaakarsu, Ahmet Buğra; Abdelfattah, Mohamed A. O.; Bakrim, Widad Ben; Khatib, Sohaib; Mahmoud, Mona F.; Bouissane, Latifa; Sobeh, Mansour (Frontiers in Nutrition, 2024)
Cubeb, Piper cubeba L., has been used for centuries in traditional medicine and culinary practices. Here, we determined the phytochemical profile, the mineral content, amino acid composition of P. cubeba berries and assessed the dermacosmeceutical properties of their water extract and essential oil (EO). A total of forty-three compounds belonging to organic acids, phenolic acids and flavonoids were found in the water extract, while 36 terpenoids were identified in the EO with Z-isoeugenol, dihydroeugenol, β-pinene, E-caryophyllene, and 1,8cineole as major constituents. The berries were found to be rich in sodium and iron, have moderate zinc content along with low contents of total nitrogen, total phosphorus, total potassium, magnesium, and calcium. Amino acid analysis revealed a higher concentration of isoleucine and leucine compared to other amino acids in the berries' extract. Evaluating the dermacosmeceutical properties of the plant's water extract and EO included assessing the antioxidant, antibacterial activities in addition to the inhibitory activities against tyrosinase and elastase enzymes. In the DPPH and FRAP assays, the water extract elicited strong antioxidant activity compared to the reference compounds. Enzyme inhibitory assays revealed that the EO had a potential to inhibit tyrosinase and elastase enzymes with IC50 values of 56.54 ± 0.19 and 64.07 ± 7.17 μg/mL, respectively. The antibacterial activity was evaluated by determining the effect of the water extract and the EO on the growth rate, biofilm formation, swimming, and swarming motilities of P. aeruginosa. It was found that the water extract and EO completely inhibited the bacterial growth at MIC of 50 mg/mL and 20%, respectively. At sub-MIC concentrations, the extract and the EO substantially reduced the biofilm formation by up to 33.36% and 79.16%, respectively as well as the swimming and swarming motilities in a dose dependent manner. Molecular docking and molecular dynamics showed that the five main components of P. cubeba oil could be the major contributors to the elastase and tyrosinase inhibitory effect. This study emphasizes the promising potential of P. cubeba as a valuable source of natural compounds that can be utilized for the development of innovative pharmaceuticals, dietary supplements, and dermacosmeceutical agents.